Domain-Specific Sedentary Behaviour and Health-Related Quality of Life by Age among Japanese Living in Malaysia - Izawa, Kazuhiro P.; Oka, Koichiro (Reviews on Recent Clinical Trials, 2022)
Background: Recently, the number of Japanese people living in Asia has increased. A previous study suggested that obesity and overweight are growing health problems both in Malaysia and worldwide that result from lifestyle changes such as a decrease in physical activity, an increase in sedentary behaviour, and poor eating habits. Objective: The purpose of the present study was to investigate the effects of differences in social demographic factors and domain-specific sedentary behaviour and health-related quality of life by age in Japanese living overseas. Methods: We surveyed 109 participants by self-entry questionnaire for social demographic factors and domain-specific sedentary behaviour by life scenario and by Short Form-36 (SF-36) for healthrelated quality of life. The subjects were divided into the ≥65 years group and <65 years group. Results: Significant differences were noted in age, employment, alcohol intake, and marital status between the groups, whereas none were noted for transportation, driving, television viewing, and smartphone/personal computer use. Work time and total sitting time of sedentary behaviour were higher, and leisure-time activity and SF-36 Mental Component Score for health-related quality of life were lower in the <65 years group. Conclusion: By assessing differences in social demographic factors and discouraging sedentary behaviour, sitting time in overseas-dwelling Japanese residents may be reduced, and effective strategies to improve health-related quality of life can be developed to combat such behaviour.
Keywords: health-related quality of life